Tracheoesophageal Fistula Caused by Tracheostomy in a Patient with Myasthenia Gravis after a Myasthenic Crisis - Jiaxin, Chen; Jingjing, Li; Kai, Zhu; Zhou, Zhou; Weibin, Liu; Haiyan, Wang; Huiyu, Feng (Frontiers in Neurology, 2017)
A 57-year-old woman with myasthenia gravis, who had experienced a myasthenic crisis, complained of coughing while drinking. At first, this appeared to be a sequela of the myasthenic crisis. However, after further investigation, the problem was identified as a tracheoesophageal fistula, a complication of tracheostomy. Here, we describe this special case in the hope that we can improve diagnostic accuracy by providing an reminder for other physicians to consider the differences between myasthenia gravis and tracheoesophageal fistula. It is very important to pay more attention to such situations in clinical scenarios and administer the most appropriate treatment without delay.